Properties of Nitrogen-Doped Nano-Crystalline Graphite Thin Films and Their Application as Electrochemical Sensors. Issue 12 (31st August 2020) - Simionescu, Octavian-Gabriel; Romanitan, Cosmin; Albu, Camelia; Pachiu, Cristina; Vasile, Eugeniu; Djourelov, Nikolay; Tutunaru, Oana; Stoian, Marius Constantin; Kusko, Mihaela; Radoi, Antonio
Abstract : Herein, several nitrogen-doped nano-crystalline graphite films (N-NCG) were prepared via plasma-enhanced chemical vapor deposition (PECVD); nano-crystalline graphite (NCG) was doped by adding ammonia gas during the PECVD growth. To develop electrochemical probes that can compete with glassy carbon (GC) electrodes for anthracene sensing, the N-NCG electrodes were systematically investigated using different techniques, including atomic force microscopy (AFM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis, Raman spectroscopy, cyclic voltammetry (CV), and differential pulsed voltammetry (DPV). The obtained sensors were tested against anthracene in an acetonitrile/water mixture (80/20 v/v) wherein the N-NCG 3 and N-NCG 5 electrochemical probes showed analytical features comparable with those of the GC electrode. The best competitor for GC was N-NCG 3 in terms of linear working range (2.5 μ M–1 mM) and sensitivity (y = 6.09 × 10 −6 + 1.21 x, r 2 = 0.9997 and y = 1.23 × 10 −5 + 0.84 x, r 2 = 0.9959 for GC and N-NCG 3, respectively).